Dramatic effect of early clopidogrel administration in reducing mortality and MACE rates in ACS patients (Swiss Medical Weekly, 2012)
BACKGROUND: Patients who have acute coronary syndromes with or without ST-segment elevation have high rates of major vascular events. We evaluated the efficacy of early clopidogrel administration (300 mg) (